Management portfelja projektov - Šelih, Jana (Projektna mreža Slovenije, 2018)
Contemporary organisations often establish multi-project environment. Those, that regularly undertake projects, have to establish system that helps them identify priority projects, as their resources are limited. The paper presents establishment of a system for evaluation of projects within an organisation, in which criteria of non-monetary nature are of significant importance. Criteria to be used are systematically identified, justified, and implemented in the multi-criteria system. Relative importance is assigned to them through established system for ranking the projects within the project portfolio. The clients operation can be rationalized by performing proposed process.
Keywords: financiranje; modeli; odločanje; organizacije; projekti